Penerapan Empat Fungsi Manajemen Pada Pengelolaan Pariwisata Bahari Berkelanjutan di Desa Jungutbatu, Kecamatan Nusa Penida - Rahadiarta, I Gede Ngurah Primanda S; Wiranatha, Agung Suryawan; Sunarta, I Nyoman (JURNAL MASTER PARIWISATA; Volume 08, Nomor 01, Juli 2021DO - 10.24843/JUMPA.2021.v08.i01.p03, 2021)
Tourism activities in Nusa Penida have experienced a very rapid increase in recent years, mainly in Jungutbatu Village, which is the village where Nusa Penida tourism began around 1970. After the transition from the seaweed farming activities in recent years, now the community relies on the tourism sector. The rapid development of marine tourism and the importance of this to the economy of the community of Jungutbatu Village, requires its management be carried out properly and sustainably. The purposes of this study were to determine the management of marine tourism in Jungutbatu Village through the application of four management functions (Planning, Organizing, Actuating, and Controlling), and to analyze tourist perceptions on the application of sustainable tourism management in Jungutbatu Village. The research approach was descriptive qualitative and data collection methods were observation, interviews, questionnaires and literature study. The results of this study indicated that the management of marine tourism in the Jungutbatu Village was carried out by involving various parties such as the community, entrepreneurs, non-governmental organizations, and the government. The planning, organizing and actuating processes that involved and accommodated the interests of various parties built a sense of responsibility and awareness to participate in the controlling process. Good management led to a good perception of tourists who came to visit, which in turn affected satisfaction and then influenced loyalty to revisit or recommend the marine tourism area of Jungutbatu Village to others. Keywords: management, perception, sustainable tourism, marine protected areas